Hotel Resort Approach to Cultural Value and The Principle of Local Architecture in Pangururan, Samosir - Fransisca J; Zahrah W (Talenta Publisher, 2019)
The shift of local architecture to global architecture and the need for tourism and relaxation are the main reasons in designing a hotel resort at Pangururan, Samosir. The hotel resort development in this location aims to preserve the culture and provide recreation and lodging facilities with a beautiful natural landscape. the design of the hotel resort is the approach to Batak Toba culture with the neo-vernacular theme. Base on the research of local culture, five main concepts applied are local material, adaptive to climate, adaptive to site contour, space and structural flexibility by providing communal areas and the using of anti-earthquake system. This design can be used as a prototype in the development of the resort hotel in the Samosir to preserve their local culture.